1987
DOI: 10.1111/j.1365-2036.1987.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid secretory capacity and plasma gastrin concentration after administration of omeprazole to normal subjects

Abstract: SUMMARY In a randomized double‐blind study, two groups of eight healthy volunteers received either placebo or omeprazole 40 mg o.m. for 14 days. Fasting plasma gastrin concentration and peak acid output in response to a maximal intravenous dose of pentagastrin were measured before, during and after the 14 days of treatment. Omeprazole caused a 68% (mean) decrease in the peak acid output when measured 24 hours after the last dose, with a simultaneous increase in the fasting plasma gastrin concentration. When me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Differences in integrated mean gastrin levels between the lansoprazole and placebo groups were significant on days 14, 16, and 18 but were not significant thereafter. Several studies have shown that although gastrin levels initially increase in response to treatment with PPIs, they plateau after several months of therapy 8,17,22,32,39,40 Other studies have shown that mean gastrin levels return to near‐baseline levels approximately 1 week after PPI therapy is discontinued, as was observed in the present study with dexlansoprazole MR 2 , 20 , 21 , 26 …”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Differences in integrated mean gastrin levels between the lansoprazole and placebo groups were significant on days 14, 16, and 18 but were not significant thereafter. Several studies have shown that although gastrin levels initially increase in response to treatment with PPIs, they plateau after several months of therapy 8,17,22,32,39,40 Other studies have shown that mean gastrin levels return to near‐baseline levels approximately 1 week after PPI therapy is discontinued, as was observed in the present study with dexlansoprazole MR 2 , 20 , 21 , 26 …”
Section: Discussionsupporting
confidence: 72%
“…Several studies have shown that although gastrin levels initially increase in response to treatment with PPIs, they plateau after several months of therapy. 8,17,22,32,39,40 Other studies have shown that mean gastrin levels return to near-baseline levels approximately 1 week after PPI therapy is discontinued, as was observed in the present study with dexlansoprazole MR. 2,20,21,26 There was a large variance in plasma gastrin AUC 24 values both at baseline and during the 3 dosing periods, which was predominantly attributable to a small number of subjects with gastrin levels that were higher at baseline than the values observed in the majority of the subjects in the study. Several of these subjects experienced moderately high gastrin levels that were 400 pg/mL or greater and/or AUC 24 values 8000 pg⋅h/ mL or greater during 1 or more of the 3 dosing periods.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…All studies investigated oral PPI administration. Four studies had a double‐blind randomized‐clinical design, 5, 17–19 the other four trials had an open label design 20–23 . Gastric acid production was measured with different methods and techniques.…”
Section: Resultsmentioning
confidence: 99%